Electronic packaging solder ball anti-oxidation coating and preparation method thereof
By forming a physical barrier and chemical protective film on the surface of the hot ball, the problem of insufficient anti-oxidation performance of the hot ball is solved, the bonding force between the hot ball is enhanced, and the requirements of high-performance electronic packaging are achieved.
Patent Information
- Application Number
- CN202510755541.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-06
- Publication Date
- 2025-08-05
AI Technical Summary
In the prior art, the electronically packaged hot balls have weak oxidation resistance, insufficient binding force between the hot balls, and complex preparation process, making it difficult to meet the needs of high-performance electronic packaging.
The polylactic acid-glycolic acid copolymer is used to form a physical barrier, and a chemical reaction with the surface of the hot balls is formed through functional additives to form a chemical protective film. The tannin acid forms a stable complex with the surface of the hot balls, enhancing the binding force between the coating and the hot balls.
It improves the antioxidant performance of the hot balls, enhances the binding force between the hot balls, reduces the risk of coating shedding, and meets the needs of high-performance electronic packaging.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electronic packaging solder balls, in particular to an anti-oxidation coating for electronic packaging solder balls and a preparation method thereof. Background Art
[0002] Electronic packaging solder balls refer to the solder balls used in electronic packaging, particularly in ball grid array (BGA) packaging. They play a crucial role as the bridge between the chip and the substrate for both electrical and mechanical connections. Tin metal, due to its low melting point and excellent conductivity, is an ideal low-temperature soldering material and is widely used in circuit connections such as high-voltage circuits, chips, and integrated circuit boards. Due to its low melting point, tin metal exhibits weak oxidation resistance and is easily oxidized in air. Over time, an oxide film forms on its surface, gradually turning it gray, dark, or black, and even producing black spots. This deteriorates the metallic luster, which in turn affects its performance, such as reduced conductivity and solderability.
[0003] Conventional coating materials and preparation methods are often used to improve the oxidation resistance of solder balls. However, these methods suffer from limited antioxidant effects, insufficient adhesion between the coating and the solder ball, and complex preparation processes, making them difficult to meet the growing demand for high-performance electronic packaging. Therefore, the present invention provides an anti-oxidation coating for solder balls in electronic packaging and a preparation method thereof. Summary of the Invention
[0004] The purpose of the present invention is to provide an anti-oxidation coating for electronic packaging solder balls and a preparation method thereof. The anti-oxidation coating prepared by the present invention not only has good anti-oxidation performance, but also can enhance the bonding strength between the coating and the solder balls, thereby effectively improving the performance of the anti-oxidation coating of the electronic packaging solder balls.
[0005] To achieve the above object, the present invention provides the following technical solution: an anti-oxidation coating for electronic packaging solder balls, comprising the following raw materials in parts by weight: 50-70 parts of anhydrous ethanol, 45-55 parts of polylactic acid-glycolic acid copolymer, 20-30 parts of deionized water, 8-10 parts of a functional additive, 2-4 parts of a cosolvent, 2-4 parts of tannic acid, and 1-3 parts of hydroxypropyl methylcellulose; The functional additive is prepared by the following method: selecting corn straw, crushing it with a hammer mill and then sieving it, adding the sieved corn straw and sulfuric acid solution to a beaker, placing the beaker in a constant temperature water bath, setting the temperature to 45°C, and continuously stirring at 150-200 r / min for 4 hours with a magnetic stirrer to obtain a reaction solution, placing the reaction solution in a centrifuge tube and centrifuging it in a centrifuge, after the treatment is completed, taking out the centrifuge tube and pouring out the supernatant in the centrifuge tube, retaining the precipitate, then adding deionized water for washing, placing the centrifuge tube in the centrifuge again, centrifuging, pouring out the supernatant, repeating the washing and centrifugation operations 3-5 times until the pH value of the washed supernatant is close to neutral, placing the washed precipitate in a dialysis bag, adding the dialysis bag and deionized water to a dialysis tank, continuously dialyzing for 24-36 hours, replacing the deionized water every 4-6 hours, until sulfate ions are no longer detected in the dialysate, and completing the preparation of the functional additive.
[0006] Preferably, the corn stalks are smaller than 150 microns after screening, and the volume ratio of the deionized water in the dialysis tank to the precipitate in the dialysis bag is (5-8):1.
[0007] Preferably, the mass ratio of the precipitate to deionized water during the centrifugal washing process is 1:3, the speed of the centrifuge is set to 4000-5000 r / min, the temperature is set to 4° C., and the washing lasts for 15-20 min.
[0008] Preferably, the polylactic acid-glycolic acid copolymer is prepared by the following method: lactic acid, glycolic acid and an organic solvent are placed in a reaction kettle, and stirred continuously at 100-300 rpm for 8-10 hours by a built-in stirrer, the temperature is set at 160°C during the stirring period, and the stirring speed is 0.5-2 L / min·m 3 Nitrogen was continuously introduced into the reactor to obtain a first mixed solution after the reaction was completed. The first mixed solution and the precipitant were added to a glass beaker, and the mixture was continuously stirred at 50-100 rpm for 30 minutes using a magnetic stirrer. The mixture was then refrigerated in a refrigerator for 12 hours, and the refrigerator temperature was set to 4°C to obtain a second mixed solution. The second mixed solution was placed in a Buchner funnel, and a vacuum pump was turned on for filtration. The vacuum degree was set to (-0.06 to -0.08 MPa) to obtain a first coagulant. The precipitant was slowly poured on the first coagulant, and gently stirred with a glass rod for 1-3 minutes. The mixture was then soaked for 10 minutes and then filtered. This was repeated 2-3 times to obtain a second coagulant. The second coagulant was placed in a tray and dried in a vacuum drying oven to obtain a polylactic acid-glycolic acid copolymer.
[0009] Preferably, the organic solvent is toluene and the precipitant is methanol.
[0010] Preferably, the mass ratio of the lactic acid, glycolic acid and organic solvent is 75:25:400.
[0011] Preferably, the volume ratio of the first mixture to the precipitant in the glass beaker is (5-10):1, and the volume ratio of the first mixture to the precipitant in the Buchner funnel is 1:3.
[0012] Preferably, the vacuum drying oven is set at a temperature of 40-60° C. and a vacuum degree of -0.08 to -0.1 MPa until drying to a constant weight.
[0013] Preferably, the concentration of the sulfuric acid solution is 6%, and the cosolvent is polyethylene glycol 400.
[0014] A method for preparing an anti-oxidation coating for electronic packaging solder balls comprises the following steps: Step 1: Weigh polylactic acid-co-glycolic acid copolymer, cosolvent, functional additive, tannic acid, hydroxypropyl methylcellulose and anhydrous ethanol as needed and add them to a reactor, set the temperature to 40-50°C, and stir at 300-500 rpm for 30-40 minutes using a built-in stirrer to obtain an initial solution; Step 2: Deionized water is weighed as needed and added to the reactor containing the initial solution, the temperature is set to 40-50°C, and the mixture is stirred at 300-500 rpm for 30-40 minutes using a built-in stirrer to obtain a coating solution; Step 3: Place the electronic packaging solder balls into a drum coating device, set the drum diameter to 30 cm, and the rotation speed to 35-40 r / min. The coating liquid prepared in step 2 is delivered to the drum through a peristaltic pump at a flow rate of 1-2 mL / min, so that the solder balls are evenly coated with the coating liquid during the rolling process in the drum. After taking out and drying, electronic packaging solder balls with an antioxidant coating are obtained.
[0015] Compared with the prior art, the present invention has the following beneficial effects: In the present invention, the continuous and dense film layer formed by using polylactic acid-glycolic acid copolymer as an auxiliary material can form a physical barrier on the surface of the tin ball, effectively isolating the tin ball from contact with oxidizing substances such as oxygen and moisture in the air, and slowing down the oxidation rate of the tin ball. The addition of functional additives further enhances the anti-oxidation ability of the coating. The active groups contained in the functional additives can chemically react with the surface of the tin ball to form a chemical protective film. At the same time, they can also capture and remove free radicals that may exist in the coating, inhibiting the occurrence of oxidation reactions. They can also fill the tiny pores in the polylactic acid-glycolic acid copolymer film layer, making the film layer structure more compact and further enhancing the barrier effect. Tannic acid has strong anti-oxidation and complexing ability, and can react with metal ions to form a stable complex on the surface of the tin ball, further enhancing the anti-oxidation effect. In the present invention, the hydroxyl polar functional groups of tannic acid and the tin atoms on the surface of the tin ball form chemical bonding anchor points through coordination bonds, hydrogen bonds, etc. The carbon chains of the polylactic acid-glycolic acid copolymer and the molecular chains of hydroxypropyl methylcellulose are entangled through intermolecular van der Waals forces to build a "molecular bridge" connecting the tin ball and the coating, thereby strengthening the interfacial bonding strength. At the same time, the polylactic acid-glycolic acid copolymer and the co-solvent have synergistic solubility, and the co-solvent molecules are inserted between the polymer molecular chains to reduce the viscosity of the system, further enhance the interfacial bonding strength, and reduce the risk of coating shedding. DETAILED DESCRIPTION
[0016] The following examples clearly and completely describe the technical solutions of the present invention. Obviously, the examples described are only some of the embodiments of the present invention, not all of them. Based on the examples of the present invention, all other embodiments obtained by persons of ordinary skill in the art without inventive effort are within the scope of protection of the present invention. It should be noted that the raw materials used in the following experiments are all commercially available. Among them, lactic acid: Product No. L100470, purchased from Aladdin Reagent Company; glycolic acid: Product No. G831000, purchased from McLean Chemical Reagent Company; hydroxypropyl methylcellulose: Product No. 9004-65-3, purchased from Guangdong Runhe Biopharmaceutical Technology Co., Ltd.; tannic acid: Product No. 403040050, purchased from McLean Chemical Reagent Company; cosolvent (polyethylene glycol 400): Product No. 2023980001, purchased from Aladdin Reagent Company; and the solder ball source is a commercially available product produced by Chongqing Qunwei Electronics Co., Ltd.
[0017] Example 1: Weigh the following raw materials in parts by weight as needed: 50 parts of anhydrous ethanol, 45 parts of polylactic acid-co-glycolic acid, 20 parts of deionized water, 8 parts of functional additives, 2 parts of cosolvents, 2 parts of tannic acid and 1 part of hydroxypropyl methylcellulose; The functional additive is prepared by the following method: corn straw is selected, crushed with a hammer mill and then sieved, the sieved corn straw and sulfuric acid solution are added to a beaker, and the beaker is placed in a constant temperature water bath, the temperature is set to 45°C, and the magnetic stirrer is used to stir continuously at 150r / min for 4 hours to obtain a reaction solution, the reaction solution is placed in a centrifuge tube and centrifuged through a centrifuge, after the treatment is completed, the centrifuge tube is taken out and the supernatant in the centrifuge tube is poured out, the precipitate is retained, and then deionized water is added for washing, the centrifuge tube is placed in the centrifuge again, centrifuged, the supernatant is poured out, the washing and centrifugation operations are repeated 3 times until the pH value of the washed supernatant is close to neutral, the washed precipitate is placed in a dialysis bag, the dialysis bag and deionized water are added to the dialysis tank, the dialysis is continued for 24 hours, the deionized water is replaced every 4 hours until sulfate ions are no longer detected in the dialysate, and the preparation of the functional additive is completed.
[0018] The corn straw is less than 150 microns after screening, and the volume ratio of deionized water in the dialysis tank and the sediment in the dialysis bag is 5:1.
[0019] During the centrifugal washing process, the mass ratio of the precipitate to deionized water was 1:3, the speed of the centrifuge was set at 4000 r / min, the temperature was set at 4°C, and the washing lasted for 15 min.
[0020] Poly(lactic acid-glycolic acid) copolymer was prepared by the following method: lactic acid, glycolic acid and an organic solvent were placed in a reactor, and stirred continuously at 100 rpm for 8 h using a built-in stirrer. The temperature was set at 160°C during the stirring period, and the stirring rate was 0.5 L / min・m 3 Nitrogen was continuously introduced into the reactor to obtain a first mixed solution after the reaction was completed. The first mixed solution and the precipitant were added to a glass beaker, and the mixture was continuously stirred at 50 rpm for 30 minutes using a magnetic stirrer. The mixture was refrigerated in a refrigerator for 12 hours, and the refrigerator temperature was set to 4°C to obtain a second mixed solution. The second mixed solution was placed in a Buchner funnel, and the vacuum pump was turned on for filtration. The vacuum degree was set to -0.06 MPa to obtain a first coagulant. The precipitant was slowly poured on the first coagulant, and gently stirred with a glass rod for 1 minute. The mixture was then soaked for 10 minutes and filtered. This was repeated twice to obtain a second coagulant. The second coagulant was placed in a tray and dried in a vacuum drying oven to obtain a polylactic acid-glycolic acid copolymer.
[0021] Toluene was used as the organic solvent and methanol was used as the precipitant.
[0022] The mass ratio of lactic acid, glycolic acid and organic solvent is 75:25:400.
[0023] The volume ratio of the first mixture to the precipitant in the glass beaker was 5:1, and the volume ratio of the first mixture to the precipitant in the Buchner funnel was 1:3.
[0024] The temperature of the vacuum drying oven was set at 40°C and the vacuum degree was set at -0.08 MPa until the sample was dried to a constant weight.
[0025] The concentration of the sulfuric acid solution is 6%, and polyethylene glycol 400 is used as a cosolvent.
[0026] A method for preparing an anti-oxidation coating for electronic packaging solder balls comprises the following steps: Step 1: Weigh poly(lactic acid-co-glycolic acid), cosolvent, functional additive, tannic acid, hydroxypropyl methylcellulose, and anhydrous ethanol as needed and add them to a reactor. Set the temperature to 40°C and stir at 300 rpm for 30 minutes using a built-in stirrer to obtain an initial solution. Step 2: Deionized water was weighed as needed and added to the reactor containing the initial solution, the temperature was set to 40°C, and the mixture was stirred at 300 rpm for 30 minutes using a built-in stirrer to obtain a coating solution; Step 3: Place the electronic packaging solder balls (solder ball particle size 0.76 mm) into the drum coating equipment, set the drum diameter to 30 cm, and the rotation speed to 35 r / min. The coating liquid prepared in step 2 is delivered to the drum through a peristaltic pump at a flow rate of 1 mL / min. The solder balls are evenly coated with the coating liquid during the rolling process in the drum. After removal, they are dried to obtain electronic packaging solder balls with an antioxidant coating.
[0027] Example 2: Weigh the following raw materials in parts by weight as needed: 60 parts of anhydrous ethanol, 50 parts of polylactic acid-co-glycolic acid, 25 parts of deionized water, 9 parts of functional additives, 3 parts of cosolvent, 3 parts of tannic acid and 2 parts of hydroxypropyl methylcellulose; The functional additive is prepared by the following method: corn straw is selected, crushed with a hammer mill and then sieved, the sieved corn straw and sulfuric acid solution are added to a beaker, and the beaker is placed in a constant temperature water bath, the temperature is set to 45°C, and the magnetic stirrer is used to stir continuously at 170r / min for 4 hours to obtain a reaction solution, the reaction solution is placed in a centrifuge tube and centrifuged through a centrifuge, after the treatment is completed, the centrifuge tube is taken out and the supernatant in the centrifuge tube is poured out, the precipitate is retained, and then deionized water is added for washing, the centrifuge tube is placed in the centrifuge again, centrifuged, the supernatant is poured out, the washing and centrifugation operations are repeated 4 times until the pH value of the washed supernatant is close to neutral, the washed precipitate is placed in a dialysis bag, the dialysis bag and deionized water are added to the dialysis tank, the dialysis is continued for 30 hours, the deionized water is replaced every 5 hours, until sulfate ions are no longer detected in the dialysate, and the preparation of the functional additive is completed.
[0028] The corn straw is less than 150 microns after screening, and the volume ratio of deionized water in the dialysis tank and the sediment in the dialysis bag is 6:1.
[0029] During the centrifugal washing process, the mass ratio of the precipitate to deionized water was 1:3, the speed of the centrifuge was set at 4500 r / min, the temperature was set at 4°C, and the washing lasted for 15-20 min.
[0030] Poly(lactic acid-glycolic acid) copolymer was prepared by the following method: lactic acid, glycolic acid and an organic solvent were placed in a reactor, stirred continuously at 200 rpm by a built-in stirrer for 9 h, the temperature was set at 160 ° C during the stirring period, and the flow rate was 1 L / min・m 3Nitrogen was continuously introduced into the reactor to obtain a first mixed solution after the reaction was completed. The first mixed solution and the precipitant were added to a glass beaker, and the mixture was continuously stirred at 75 rpm for 30 minutes using a magnetic stirrer. The mixture was then refrigerated in a refrigerator for 12 hours, and the refrigerator temperature was set to 4°C to obtain a second mixed solution. The second mixed solution was placed in a Buchner funnel, and the vacuum pump was turned on for filtration. The vacuum degree was set to -0.07 MPa to obtain a first coagulant. The precipitant was slowly poured on the first coagulant, and gently stirred with a glass rod for 2 minutes. The mixture was then soaked for 10 minutes and filtered. This was repeated 3 times to obtain a second coagulant. The second coagulant was placed in a tray and dried in a vacuum drying oven to obtain a polylactic acid-glycolic acid copolymer.
[0031] Toluene was used as the organic solvent and methanol was used as the precipitant.
[0032] The mass ratio of lactic acid, glycolic acid and organic solvent is 75:25:400.
[0033] The volume ratio of the first mixture to the precipitant in the glass beaker was 7:1, and the volume ratio of the first mixture to the precipitant in the Buchner funnel was 1:3.
[0034] The temperature of the vacuum drying oven was set at 50°C and the vacuum degree was set at -0.09 MPa until the sample was dried to a constant weight.
[0035] The concentration of the sulfuric acid solution is 6%, and polyethylene glycol 400 is used as a cosolvent.
[0036] A method for preparing an anti-oxidation coating for electronic packaging solder balls comprises the following steps: Step 1: Weigh poly(lactic acid-co-glycolic acid), cosolvent, functional additive, tannic acid, hydroxypropyl methylcellulose, and anhydrous ethanol as needed and add them to a reactor. Set the temperature to 45°C and stir at 400 rpm for 35 minutes using a built-in stirrer to obtain an initial solution. Step 2: Deionized water was weighed as needed and added to the reactor containing the initial solution, the temperature was set to 45°C, and the mixture was stirred at 400 rpm for 35 minutes using a built-in stirrer to obtain a coating solution; Step 3: Place the electronic packaging solder balls into a drum coating device, set the drum diameter to 30 cm and the rotation speed to 37 r / min, and deliver the coating liquid prepared in step 2 to the drum through a peristaltic pump at a flow rate of 2 mL / min. Allow the solder balls to be evenly coated with the coating liquid while rolling in the drum. Take them out and dry them to obtain electronic packaging solder balls with an antioxidant coating.
[0037] Example 3: Weigh the following raw materials in parts by weight as needed: 70 parts of anhydrous ethanol, 55 parts of polylactic acid-co-glycolic acid, 30 parts of deionized water, 10 parts of functional additives, 4 parts of cosolvent, 4 parts of tannic acid and 3 parts of hydroxypropyl methylcellulose; The functional additive is prepared by the following method: corn straw is selected, crushed with a hammer mill and then sieved, the sieved corn straw and sulfuric acid solution are added to a beaker, and the beaker is placed in a constant temperature water bath, the temperature is set to 45°C, and the mixture is stirred continuously at 200 r / min by a magnetic stirrer for 4 hours to obtain a reaction solution, the reaction solution is placed in a centrifuge tube and centrifuged by a centrifuge, after the treatment is completed, the centrifuge tube is taken out and the supernatant in the centrifuge tube is poured out, the precipitate is retained, and then deionized water is added for washing, the centrifuge tube is placed in the centrifuge again, centrifuged, the supernatant is poured out, the washing and centrifugation operations are repeated 5 times until the pH value of the washed supernatant is close to neutral, the washed precipitate is placed in a dialysis bag, the dialysis bag and deionized water are added to the dialysis tank, the dialysis is continued for 36 hours, the deionized water is replaced every 6 hours, until sulfate ions are no longer detected in the dialysate, and the preparation of the functional additive is completed.
[0038] The corn straw is less than 150 microns after screening, and the volume ratio of deionized water in the dialysis tank and the sediment in the dialysis bag is 8:1.
[0039] During the centrifugal washing process, the mass ratio of the precipitate to deionized water was 1:3, the speed of the centrifuge was set at 5000 r / min, the temperature was set at 4°C, and the washing lasted for 20 min.
[0040] Poly(lactic acid-glycolic acid) copolymer was prepared by the following method: lactic acid, glycolic acid and an organic solvent were placed in a reactor, stirred continuously at 300 rpm for 10 h by a built-in stirrer, the temperature was set at 160 ° C during the stirring period, and the stirring speed was 2 L / min・m 3 Nitrogen was continuously introduced into the reactor to obtain a first mixed solution after the reaction was completed. The first mixed solution and the precipitant were added to a glass beaker, and the mixture was continuously stirred at 100 rpm for 30 minutes using a magnetic stirrer. The mixture was then refrigerated in a refrigerator for 12 hours, and the refrigerator temperature was set to 4°C to obtain a second mixed solution. The second mixed solution was placed in a Buchner funnel, and the vacuum pump was turned on for filtration. The vacuum degree was set to -0.08 MPa to obtain a first coagulant. The precipitant was slowly poured on the first coagulant, and gently stirred with a glass rod for 3 minutes. The mixture was then soaked for 10 minutes and filtered. This was repeated 3 times to obtain a second coagulant. The second coagulant was placed in a tray and dried in a vacuum drying oven to obtain a polylactic acid-glycolic acid copolymer.
[0041] Toluene was used as the organic solvent and methanol was used as the precipitant.
[0042] The mass ratio of lactic acid, glycolic acid and organic solvent is 75:25:400.
[0043] The volume ratio of the first mixture to the precipitant in the glass beaker was 10:1, and the volume ratio of the first mixture to the precipitant in the Buchner funnel was 1:3.
[0044] The temperature of the vacuum drying oven was set at 60°C and the vacuum degree was set at -0.1 MPa until the sample was dried to a constant weight.
[0045] The concentration of the sulfuric acid solution is 6%, and polyethylene glycol 400 is used as a cosolvent.
[0046] A method for preparing an anti-oxidation coating for electronic packaging solder balls comprises the following steps: Step 1: Weigh poly(lactic acid-co-glycolic acid), cosolvent, functional additive, tannic acid, hydroxypropyl methylcellulose, and anhydrous ethanol as needed and add them to a reactor. Set the temperature to 50°C and stir at 500 rpm for 40 minutes using a built-in stirrer to obtain an initial solution. Step 2: Deionized water was weighed as needed and added to the reactor containing the initial solution, the temperature was set to 50°C, and the mixture was stirred at 500 rpm for 40 minutes using a built-in stirrer to obtain a coating solution; Step 3: Place the electronic packaging solder balls into a drum coating device, set the drum diameter to 30 cm and the rotation speed to 40 r / min, and deliver the coating liquid prepared in step 2 to the drum through a peristaltic pump at a flow rate of 2 mL / min. Allow the solder balls to be evenly coated with the coating liquid during the rolling process in the drum. Take them out and dry them to obtain electronic packaging solder balls with an antioxidant coating.
[0047] Comparative Example 1: The difference between this comparative example and Experiment 1 is that no copolymerization reaction of glycolic acid was carried out in this comparative example.
[0048] Comparative Example 2: The difference between this comparative example and Experiment 1 is that no functional additive is added in this comparative example.
[0049] Comparative Example 3: The difference between this comparative example and Experiment 1 is that no tannic acid was added in this comparative example.
[0050] Performance test: The electronic packaging solder balls with anti-oxidation coatings prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were subjected to performance tests: Performance tests include: Anti-oxidation performance test: Referring to GB / T10125-2021 Artificial Atmosphere Corrosion Test Salt Spray Test, the solder balls were placed in a constant temperature and humidity chamber (85°C / 85%RH) for accelerated oxidation for 168 hours, and the mass gain rate (oxidation weight gain percentage) was measured after removal; Coating adhesion test: Conduct a 100-grid test (1mm x 1mm grid) according to GB / T9286-2021 Paint and Varnish Cross-cut Test. Use 3M tape to peel off the adhesive and calculate the percentage of the peeled area. Coating corrosion resistance test: According to GB / T2423.17-2008 Salt spray test method for electrical and electronic products, conduct a 5% NaCl neutral salt spray test for 72 hours and observe the percentage of surface rust area; The obtained test data are recorded in the following table:
[0051] Comparing and analyzing the relevant data in the table shows that the anti-oxidation coating prepared using the electronic packaging solder ball anti-oxidation coating and preparation method of the present invention not only has excellent antioxidant properties, but also enhances the bonding strength between the coating and the solder ball, effectively improving the performance of the anti-oxidation coating of the electronic packaging solder ball. This demonstrates that the electronic packaging solder ball anti-oxidation coating and preparation method provided by the present invention have a broader market prospect and are more suitable for promotion.
Claims
1. An anti-oxidation coating for electronic packaging solder balls, characterized by: The invention comprises the following raw materials in parts by weight: 50-70 parts of anhydrous ethanol, 45-55 parts of polylactic acid-glycolic acid copolymer, 20-30 parts of deionized water, 8-10 parts of functional additives, 2-4 parts of cosolvents, 2-4 parts of tannic acid and 1-3 parts of hydroxypropyl methylcellulose; The functional additive is prepared by the following method: selecting corn straw, crushing it with a hammer mill and then sieving it, adding the sieved corn straw and sulfuric acid solution to a beaker, placing the beaker in a constant temperature water bath, setting the temperature to 45°C, and continuously stirring at 150-200 r / min for 4 hours with a magnetic stirrer to obtain a reaction solution, placing the reaction solution in a centrifuge tube and centrifuging it in a centrifuge, after the treatment is completed, taking out the centrifuge tube and pouring out the supernatant in the centrifuge tube, retaining the precipitate, then adding deionized water for washing, placing the centrifuge tube in the centrifuge again, centrifuging, pouring out the supernatant, repeating the washing and centrifugation operations 3-5 times until the pH value of the washed supernatant is close to neutral, placing the washed precipitate in a dialysis bag, adding the dialysis bag and deionized water to a dialysis tank, continuously dialyzing for 24-36 hours, replacing the deionized water every 4-6 hours, until sulfate ions are no longer detected in the dialysate, and completing the preparation of the functional additive.
2. The electronic packaging solder ball anti-oxidation coating according to claim 1, characterized in that: The corn stalks are less than 150 microns after screening, and the volume ratio of the deionized water in the dialysis tank to the sediment in the dialysis bag is (5-8):
1.
3. The electronic packaging solder ball anti-oxidation coating according to claim 1, characterized in that: During the centrifugal washing process, the mass ratio of the precipitate to deionized water is 1:3, the speed of the centrifuge is set at 4000-5000 r / min, the temperature is set at 4° C., and the washing lasts for 15-20 minutes.
4. The anti-oxidation coating for electronic packaging solder balls according to claim 1, characterized in that: The polylactic acid-glycolic acid copolymer is prepared by the following method: lactic acid, glycolic acid and an organic solvent are placed in a reaction kettle, and stirred continuously at 100-300 rpm for 8-10 hours by a built-in stirrer, the temperature is set at 160° C. during the stirring period, and the stirring speed is 0.5-2 L / min·m 3 Nitrogen is continuously introduced into the reactor to obtain a first mixed solution after the reaction is completed. The first mixed solution and the precipitant are added to a glass beaker, and the mixture is continuously stirred at 50-100 rpm for 30 minutes using a magnetic stirrer. The mixture is then refrigerated in a refrigerator for 12 hours, and the refrigerator temperature is set to 4°C to obtain a second mixed solution. The second mixed solution is placed in a Buchner funnel, and a vacuum pump is turned on for filtration. The vacuum degree is set to (-0.06 to -0.08 MPa) to obtain a first coagulant. The precipitant is slowly poured on the first coagulant, and the mixture is gently stirred with a glass rod for 1-3 minutes. The mixture is then soaked for 10 minutes and filtered. This is repeated 2-3 times to obtain a second coagulant. The second coagulant is placed in a tray and dried in a vacuum drying oven to obtain a polylactic acid-glycolic acid copolymer.
5. The electronic packaging solder ball anti-oxidation coating according to claim 4, characterized in that: The organic solvent is toluene, and the precipitant is methanol.
6. The electronic packaging solder ball anti-oxidation coating according to claim 4, characterized in that: The mass ratio of the lactic acid, glycolic acid and organic solvent is 75:25:
400.
7. The electronic packaging solder ball anti-oxidation coating according to claim 4, characterized in that: The volume ratio of the first mixture to the precipitant in the glass beaker is (5-10):1, and the volume ratio of the first mixture to the precipitant in the Buchner funnel is 1:
3.
8. The electronic packaging solder ball anti-oxidation coating according to claim 4, characterized in that: The vacuum drying oven is set at a temperature of 40-60° C. and a vacuum degree of -0.08 to -0.1 MPa until drying to a constant weight.
9. The electronic packaging solder ball anti-oxidation coating according to claim 1, characterized in that: The concentration of the sulfuric acid solution is 6%, and the cosolvent is polyethylene glycol 400.
10. A method for preparing an anti-oxidation coating for electronic packaging solder balls according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1: Weigh polylactic acid-co-glycolic acid copolymer, cosolvent, functional additive, tannic acid, hydroxypropyl methylcellulose and anhydrous ethanol as needed and add them to a reactor, set the temperature to 40-50°C, and stir at 300-500 rpm for 30-40 minutes using a built-in stirrer to obtain an initial solution; Step 2: Deionized water is weighed as needed and added to the reactor containing the initial solution, the temperature is set to 40-50°C, and the mixture is stirred at 300-500 rpm for 30-40 minutes using a built-in stirrer to obtain a coating solution; Step 3: Place the electronic packaging solder balls into a drum coating device, set the drum diameter to 30 cm, and the rotation speed to 35-40 r / min. The coating liquid prepared in step 2 is delivered to the drum through a peristaltic pump at a flow rate of 1-2 mL / min, so that the solder balls are evenly coated with the coating liquid during the rolling process in the drum. After taking out and drying, electronic packaging solder balls with an antioxidant coating are obtained.